Treatment as Prevention for Hepatitis C (TraP HepC). A Real-world Experience from the First 12 Months of a Nationwide Elimination Program in Iceland. (4th October 2017) - Gottfredsson, Magnus; Tyrfingsson, Thorarinn; Runarsdottir, Valgerdur; Bergmann, Ottar M; Bjornsson, Einar S; Johannsson, Birgir; Sigurdardottir, Bryndis; Fridriksdottir, Ragnheidur H; Löve, Arthur; Löve, Thorvardur J; Sigmundsdottir, Gudrun; Heimisdottir, Maria; et al.
Abstract: Background: Hepatitis C virus (HCV) infection is associated with significant morbidity and mortality. Iceland, an island with a population of 330, 000 has a HCV seroprevalence of 0.3% and an estimated total of 800–1000 patients. There is good access to health care among people who inject drugs (PWID) and Iceland thus serves as an ideal setting for a proof of concept intervention, aiming for elimination of the disease as a public health threat. If elimination is to be achieved PWID, who are key drivers of transmission, need to be a focus of treatment scale up. Methods: All patients in the country infected with HCV were offered direct-acting antiviral agents (DAAs) starting in 01/2016. The regimens are chosen according to national guidelines; SOF/LDV +/−RBV through October 2016 and SOF/VEL +/− RBV thereafter. People with recent injection drug use (IDU), prisoners and patients with advanced liver disease are prioritized. PWID receive additional support to facilitate compliance. Various strategies are employed to enhance case detection and harm reduction. The goal is to initiate treatment for every patient in Iceland within 36 months (end-2018), aiming for elimination of domestic transmission of HCV. Results: Twelve months after launching the nationwide program 527 patients had been evaluated, 53–66% of the estimated total patient population. The mean age is 42 years (range, 17–70 years, 2 males to every female). The reported main route of infection was IDU (90%). At the time of evaluation, 33% reported recent (within 6 months) IDU, 6% were homeless, and 5% in prison. Stimulants were the preferred IV drug among 84% of PWID but opiates by only 14%; overall 15% were receiving opiate substitution therapy (OST). During the first 12 months of the study period treatment with DAAs was initiated in 480 patients and 322 were scheduled to complete protocol. Drop-out rate is 6.5%. Sustained virological response at 12 weeks (SVR12) for the entire group, including patients who dropped out or are lost to follow-up is 90%. It is significantly lower among the homeless (60%) and active IDU (83% vs. 93%, P  = 0.007). Conclusion: A relatively large proportion of HCV infected patients in the community, including people actively injecting drugs, can be initiated on treatment in a short period of time. Current drug use does not preclude treatment success. Disclosures: M. Gottfredsson, Gilead: Grant Investigator and Scientific Advisor, Consulting fee and Research support; Astellas: Consultant, Speaker honorarium